Audit of sustainability report and sustainable finance: An agriculture case in the Indonesian Stock Exchange - Suryatimur, Kartika Pradana; Nurcahya, Yulida Army; Simamora, Alex Johanes; Susilo, Ghina Fitri Ariesta; Muqorobin, Masculine Muhammad; Utami, Martiana Riawati; Dewantara, Ghiyats Furqan (Universitas Muhammadiyah Yogyakarta, Indonesia, 2025)
Research aims: This research aims to examine the effect of the audit of sustainability reports on sustainable finance in agriculture companies.Design/Methodology/Approach: This research used 13 agriculture companies listed on the Indonesian Stock Exchange from 2021-2023 as the sample. While the sustainability report audit was measured by a dummy variable, sustainable finance was measured by scoring elements of growth, bankruptcy profile, risk profile, and value creation. Data analysis employed multiple regression.Research findings: Based on data analysis, an audit of sustainability reports improves sustainable finance. The presence of an independent audit functions as a quality certification, increasing the perceived legitimacy and trustworthiness of sustainability disclosures. This can enhance stakeholders' confidence in the firm's governance, risk management, and ethical commitment—factors increasingly linked to financial sustainability (e.g., access to capital, lower cost of financing, and long-term investor trust). Theoretical contribution/Originality: First, this research contributes to the literature by extending the signaling theory framework to the context of sustainability report audits and sustainable finance. Second, the study provides new evidence on the relationship between sustainability report audits and sustainable financial performance. Third, the research introduces a novel perspective in terms of sample selection, focusing on agricultural companies. Fourth, this study provides a comprehensive overview of integrating key regulatory frameworks, namely Regulation of Indonesian Financial Services Authority No. 51/POJK.03/2017, Circular Letter of Indonesian Financial Services Authority No. 16 /SEOJK.04/2021, and Indonesian Law No. 2 of 2019.